“Making the Unusual Usual:” Students’ Perspectives and Experiences of Learning at Home during the COVID-19 Pandemic - Mary Beth Schaefer; Sandra Schamroth Abrams; Molly Kurpis; Madeline Abrams; Charlotte Abrams (Middle Grades Review, 2020)
This child-parent research is a student-led inquiry into three adolescent girls’ experiences of learning during the age of COVID-19 shelter-in-place mandate. In this collaborative autoethnography, a research team of five (three adolescent researchers—two of whom are sisters—and their respective mothers) met via videoconference to engage in five rounds of inductive and deductive data collection and analyses. Findings capture the three adolescents’ experiences of new teaching methods in new learning spaces: (1) the physical space of “Doing School at Home-How it feels;” (2) the negotiations undertaken by the girls called “Improvisation and a School Mindset;” and (3) the need to respond to one constant: “Everything is Always Changing.” A fourth theme, called “Being at Home Gives Me...” was created to capture the human experience of doing school at home–and the new spaces that opened up. Recommendations to help make school work in the home space are provided.
Keywords: child-parent research; collaborative autoethnography; pandemic pedagogy; learning-at-home; COVID-19